Islamic Psychology as a Solution for Students' Mental Health in the Modern Era - M Iqbal Abdurrohman; Muhammad Adip (Maklumat: Journal of Da'wah and Islamic Studies, 2025)
The phenomenon of mental health among students is increasing in the modern era. Academic pressure, the influence of social media, social change, and lack of spiritual support are dominant factors that cause stress, anxiety, and depression. This article examines the role of Islamic psychology as a solution to overcome students' mental health problems. The research method used is library research with data analysis from various literature sources related to the concept of Islamic psychology, challenges to students' mental health, and solutions offered by Islamic psychology. The results of the study show that the Islamic psychology approach provides a holistic solution that includes spiritual, emotional, and physical aspects. Methods such as prayer, dhikr, reading the Qur'an, and Islamic moral development have proven effective in helping students achieve peace of mind and overcome mental health disorders. By implementing Islamic psychology values, students can be better prepared to face the pressures of life and improve their mental and spiritual quality amidst the development of the times.